Water Diplomacy and Water Disputes in the Maghreb Region - Dehshiri, Mohammadreza; Hekmatara, Hamed (Technium Social Sciences Journal, 2020)
In recent decades, with the rapid growth of the population of the Maghreb low-water region, the countries of this region have begun to make the most of their water resources. In this regard, the importance of the transboundary water resources of the region has been increased and disputes over these common resources have been gradually developed. Due to the historical political differences between some of the important countries in the Maghreb region, the lack of integrated water resources management and lack of sharing data has made it extremely difficult to form joint committees to oversee transboundary water resources as well as to negotiate the management of these waters; While conventions and initiatives that the countries of the region are members of them, can provide good conditions for water diplomacy and cooperation at the regional level and capacities should be used.